Propuesta para la creación de un museo especializado en la cultura Samaria (2021)
The cultural industry, and especially museums, constantly face the challenge of innovation, content development, choice of themes, and memory preservation. Therefore, when creating a museum, it is essential to strategically plan the design of activities, actions and measures aimed at its sustainability. That is why this research aims to plan the creation of an interactive museum in the city of Santa Marta, in favor of promoting cultural identity in the local community and making cultural and historical tourism visible to visitors and tourists, given the great offer due to cultural interest that is presented today and the notorious lack of interactive cultural spaces that satisfy the need. The value proposition of this research is to strategically propose an interactive experience center that allows learning about the cultural and historical heritage of the Santa Marta District, through the use of new technological tools that generate cultural and experiential activities. Thus, allowing the local cultural heritage of this city to be made even more visible and preserved over time so that future generations can know and enjoy the same material and intangible heritage that is available today. In this sense, this work has a descriptive research methodology with a quantitative approach, which seeks to carry out an analysis of the behavior of multiple people concerning the implementation of new museums and to know their expectations in a percentage way. In turn, it provides and details the general parameters that must be taken into account when planning and creating museums, to meet the proposed objective.